Addition of metformin to anti-PD-1/PD-L1 drugs activates anti-tumor immune response in peripheral immune cells of NSCLC patients - Luisa Amato; Caterina De Rosa; Gaetano Di Guida; Filippo Sepe; Annalisa Ariano; Sara Capaldo; Faiz Ul Haq; Alessandra Di Liello; Concetta Tuccillo; Stefano Lucà; Renato Franco; Viviana De Rosa; et al. (Cell Death and Disease)
Abstract Immunotherapy has transformed the treatment landscape for non-small cell lung cancer (NSCLC), yet achieving lasting benefits remains a challenge. The resistance mechanisms to immunotherapy are complex, involving interactions between tumor cells and immune cells that are not fully understood. Metformin, an FDA-approved diabetes medication, shows promise in enhancing immunotherapy efficacy by boosting anti-tumor immune responses, although the underlying molecular pathways are still being investigated. This study utilized co-culture models of cancer and immune cells to explore the effects of combining metformin with anti-PD-1/PD-L1 therapies on the anti-tumor immune response in LKB1 mutant (LKB1mut) versus wild-type (LKB1wt) NSCLC cells, alongside peripheral blood immune cells from NSCLC patients. The transcriptomic profiles of LKB1mut and LKB1wt NSCLC cells were characterized via bulk RNA sequencing to understand gene expression changes induced by metformin. Patients with advanced-stage NSCLC provided peripheral blood mononuclear cells (PBMCs) for analysis. The study assessed metformin’s impact both alone and in combination with anti-PD-1/PD-L1 agents on innate immune pathways. Results indicated that metformin activated the cGAS-STING pathway and interferons in PBMCs, enhancing their anti-tumor capabilities. Notably, immune cells treated with metformin and immunotherapy exhibited synergistic effects, significantly reducing colony formation in LKB1mut NSCLC cells. Additionally, monocytes from NSCLC patients showed decreased viability of NSCLC cells in co-culture, independent of LKB1 status, and shifted towards an anti-tumor M1 phenotype with combined treatment. These findings were supported by 3D co-culture models involving tumor spheroids and patient-derived organoids, highlighting a novel biological rationale for using metformin alongside immunotherapeutic agents to boost anti-tumor activity across various immune cell subsets derived from NSCLC patients.